Thermal Analysis Of Three Phase Induction Motor - حسن عزت; بدر زيد; زيتي همام (Latakia University Journal -Engineering Sciences Series, 2021)
This paper provides an explanation of two of the analytical methods used in thermal analysis of the induction motor. The thermodynamic analysis is performed on a three phase Totally Enclosed Fan-Cooled (TEFC) induction motor according to the combined parameter method, which assumes that whatever parameter in any object can be studied on one point of this object that represents to the mean parameter point. The thermal equations are modeled using MATLAB. In order to use the ANSYS program that adopts the finite element method in the thermal analysis process Then the motor is designed using MAXWEL software. An analytical calculation of the motor is performed using Ansoft RMxprt package to find out its efficiency and basic parameters, and moving Maxwell 2D package that allows to use ANSYS software in order to perform thermal analysis of the motor. By comparing the thermal analysis results for both methods, it was found that the finite element method (ANSYS) gives more accurate results in thermal analysis due to the circumferential heat flow is ignored when the combined parameter method is used